A world without heroes - Mull, Brandon (New York : Aladdin, 2012)
Fourteen-year-old Jason Walker is transported to a strange world called Lyrian, where he joins Rachel, who was also drawn there from our world, and a few rebels, to piece together the Word that can destroy the malicious wizard emperor, Surroth.
Keywords: Heroes -- Fiction; Fantasy fiction